The flipped class as a proposal for learning English - Julio Christian Jiménez Carrillo (Universidad Ciencia y Tecnología, 2024)
The study addressed the effectiveness of the flipped classroom in learning English, using an applied-experimental quantitative approach with a quasi-experimental design. The sample of 30 high school students was selected through non-probabilistic convenience sampling. An objective assessment was used to measure English comprehension levels, and the data analysis technique consisted of a non-parametric Mann-Whitney U test to test the research hypothesis. After implementing the flipped classroom program, the results revealed superior performance in the experimental group, highlighting the program's effectiveness and relevance in improving and acquiring linguistic skills in English by the students.